(untitled) (Research, Society and Development, 2022)
The high demand for beans has driven the adoption of techniques aimed at increasing productivity without increasing the planted area. The present work was inserted in this context with the objective of evaluating the germination, emergence and initial growth of common bean under different products and doses of biostimulants. The research was conducted at Sítio Monte Alegre, in Carvalhópolis, in the southern region of Minas Gerais, from June to August 2022. The experimental design was in a completely randomized design (DIC), in a 4x2 factorial scheme with three replications. The experimental factors consisted of different concentrations of biostimulating substances (0; 0.1; 0.2; 0.4 ml/kg) and commercial biostimulating substances (Stimulate®; C3®). After this period, the bean seeds were sown in polypropylene pots with a volume of 1 liter with Carolina Soil. In the period of fifteen days, the characteristics of germination were evaluated; Germination Speed ​​Index (GVI); Average total length of seedlings; Average root length; Average shoot length; Dry biomass of aerial part. The biostimulants Bioestimulate® promoted a greater increase in root development than the biostimulant C3®. For emergence speed, development of the root system and aerial part and bean biomass, the addition of biostimulants had a quadratic effect, with doses close to 0.2 ml kg-1 showing greater capacity for increment in the variables analyzed.